Knowledge and attitude of visitor on triage system in emergency room at Patan hospital, Nepal - Rijal, Suraj; Adhikari, Sunil (Journal of General Practice and Emergency Medicine of Nepal, 2019)
Introduction: Emergency triage is the process by which patient is classified according to the type and urgency of their conditions to get the right patient to the right place at the right time with the right care provider. It is important that patient and visitor knows about the triage. This study is conducted to analyse knowledge and attitude of visitor on triage system. Method: It is a cross-sectional descriptive study carried out in Patan Hospital Emergency Department on 2016 July 1st to 2016 September 15. Patients were interviewed with self-structured questionnaire. Result: Total 384 participants completed the self-structured knowledge and attitude questions and descriptive analysis done using SPSS-17. 280(73%) participants thought that triaging every patient entering emergency room is important.262(69.50%) participants answered that the purpose of triage is for efficient identifying sick patient and prompt management. Conclusion: The knowledge and attitude of the visitor about triage is fairly good contrary to assumption